2013
DOI: 10.1186/1476-0711-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Aquilaria crassna leaf extract against Staphylococcus epidermidis by disruption of cell wall

Abstract: BackgroundAquilaria crassna Pierre ex Lecomte has been traditionally used in Thailand for treatment of infectious diseases such as diarrhoea and skin diseases for a long time. The main objectives of this study were to examine antibacterial activity of the Aquilaria crassna leaf extract against Staphylococcus epidermidis and its underlying mechanism. The antioxidant activity and acute toxicity were studied as well.MethodsAntioxidant activities were examined by FRAP, ABTS and DPPH scavenging methods. Antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 18 publications
4
85
0
Order By: Relevance
“…In the present study, extracts of Z. marina L., especially the ethyl acetate fraction, showed good antibacterial activity against Gram positive bacteria, but had no effect on Gram negative bacteria. The antibacterial activity of ethyl acetate fraction against S. aureus is higher than that of ethanol extract of Ecballium elaterium (Adwan et al, 2011), but the activity against S. epidermidis is little lower than that of water extract of Aquilaria crassna (Kamonwannasit et al, 2013). B. anthracis is much more sensitive to ethyl acetate fraction of Z. marina L. than that of stem bark crude extract of Antidesma venosum (Mwangomo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, extracts of Z. marina L., especially the ethyl acetate fraction, showed good antibacterial activity against Gram positive bacteria, but had no effect on Gram negative bacteria. The antibacterial activity of ethyl acetate fraction against S. aureus is higher than that of ethanol extract of Ecballium elaterium (Adwan et al, 2011), but the activity against S. epidermidis is little lower than that of water extract of Aquilaria crassna (Kamonwannasit et al, 2013). B. anthracis is much more sensitive to ethyl acetate fraction of Z. marina L. than that of stem bark crude extract of Antidesma venosum (Mwangomo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of aqueous, ethanolic and methanolic extracts were determined by serial dilution method (Kamonwannasit et al 2013). To determine MIC, extract dilution series of 20 to 300 mg ml -1 were prepared.…”
Section: Determination Of (Mic) and (Mbc) By Serial Dilution Methodsmentioning
confidence: 99%
“…Table 2 illustrates a strong correlation between saponins of carrot peel and ARSC (R 2 = 0.78), while TPC of carrot peel weakly correlated with ARSC (R 2 = 0.25), meaning that saponins were a major contributor to ARSC of carrot peel, which might promote single electron transfer capacity for ABTS free radical to form an electron pair [17]. The study of Dhanani et al [35] indicated that the ethanolic extract of W. somnifera possessed the highest ARSC in comparison with the extracts obtained by 10% ethanol and water, while the study of Kamonwannasit et al [36] found that the water extract of A. crassna leaves substantially exhibited the ARSC (IC 50 = 218.93 µg/mL) when compared to butylated hydroxytoluene (BHT; IC 50 = 83.09 µg/mL). These results showed that solvents significantly affected ARSC of carrot peel, in which water was the best solvent for obtaining the optimal ARSC from carrot peel.…”
Section: Individual Bioactive Compounds Within Carrot Rootmentioning
confidence: 98%